2020
DOI: 10.1177/2050312120902591
|View full text |Cite
|
Sign up to set email alerts
|

A survey of syphilis knowledge among medical providers and students in Rhode Island

Abstract: Background: In the United States, syphilis cases have increased dramatically over the last decade. Recognition and timely diagnosis by medical providers are essential to treating syphilis and preventing further transmission. Methods: From 2016 to 2017, a cross-sectional survey was performed among medical students, residents, fellows, and attending physicians in Rhode Island. Topics included demographics, level of medical training, experience diagnosing and treating syphilis, and familiarity with the reverse te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…But, findings of a similar survey-based study conducted with medical students, fellows and attending physicians revealed that overall syphilis knowledge was low and need for education and clinical training to promote syphilis management. 13 Therefore, we anticipate that the knowledge gaps identified in dentists in Turkey likely exist in other countries, and/or healthcare professions other than dentists as well. It should also be considered as another limitation that the cross-sectional design of this study does not allow to determine the causality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, findings of a similar survey-based study conducted with medical students, fellows and attending physicians revealed that overall syphilis knowledge was low and need for education and clinical training to promote syphilis management. 13 Therefore, we anticipate that the knowledge gaps identified in dentists in Turkey likely exist in other countries, and/or healthcare professions other than dentists as well. It should also be considered as another limitation that the cross-sectional design of this study does not allow to determine the causality.…”
Section: Discussionmentioning
confidence: 99%
“…• "Extra-oral Clinical Features," • "Oral Findings," • "Diagnosis & Treatment" of syphilis. [12][13][14] As part of the final section, participants were asked two questions based on a 5-point Likert scale 15,16 to assess how comfortable they were taking anamnesis with respect to a patient's sexual behavior (Table 1). The scale scores and their interpretations were as 0: never/1: rarely/2: sometimes/ 3: frequently/4: always.…”
Section: Data Collectionmentioning
confidence: 99%
“…19 Lastly, "adequate plus" therapy may reflect lack of knowledge regarding management of syphilis among treating providers. 23 Educational efforts and continued evaluation of practice styles are needed given concerns about cost, availability, and antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…“Adequate plus” treatment was notably higher for treatment of early syphilis involving PLWH, which could reflect slow adaptation to changes as the 1993 guidelines allowed for extra doses of penicillin for PLWH at the providers discretion 19 . Lastly, “adequate plus” therapy may reflect lack of knowledge regarding management of syphilis among treating providers 23 . Educational efforts and continued evaluation of practice styles are needed given concerns about cost, availability, and antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto al nivel de conocimientos, considerado regular, nuestros resultados son similares a lo publicado en estudios previos desarrollados en personal sanitario de Brasil, Colombia y Estados Unidos (9,11,12). El hallazgo de los mejores niveles de conocimientos en los médicos residentes y el bajo nivel en enfermeras también fue descrito en hospitales de Teresina (Brasil) por Rodrigues et al en 2018 (13), quienes postulan que esta situación podría estar relacionada con la mayor rotación del personal de enfermería, que probablemente estaría menos familiarizado con los protocolos.…”
Section: Discussionunclassified